ANALISIS PENETAPAN PERATURAN DAERAH NOMOR 18 TAHUN 2017 TENTANG APBD KABUPATEN SINJAI TAHUN ANGGARAN 2018 - Suyuti, Muhammad (Al Qisthi: Jurnal Sosial dan Politik, 2019)
This research aims to determine the interaction of actors (Local Government and Regional Budget/APBD) Sinjai District in the discussion and determination of the Budget District Sinjai Fiscal year 2018. This reseach is also aimed to know the process of discussion of the draft of regulation about APBD of Sinjai Regency 2018 based on the regulation of Minister of Home Affairs No. 33 the year 2017 about Guidance of Budget formation of fiscal year 2018. This research was conducted in DPRD of Sinjai Regency with a research base used in this research is qualitative research by using descriptive research type. This research illustrates in depth the interaction between DPRD members and the Regional Government of Sinjai District along with their staffs in the process of discussion and determination of the Sinjai District Budget for Fiscal Year 2018. Research data obtained from the members of the Regional House of Sinjai, Chairman of The Commission of DPRD Sinjai and leaders of the Organization of Regional Devices. The results of the research indicate that the process of deliberation on the draft of Regional Regulation concerning APBD of Sinjai Regency is inconsistent with the regulation of the Minister of Home affairs No. 33 year 2017 Concering Guidelines for the Preparation of APBD for Budget year 2018. The agreement between DPRD and Local Government of Sinjai Regency toward the draft of Local Regulation Concerning APBD of Sinjai Regency Budget Year 2018 on November 30, 2018 is in accordance with Regulation of Minister of Home Affairs No.33 year 2017 about Guidance of Depreciation of APBD of Fiscal Year 2018.